1961
DOI: 10.1021/je60011a041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chemical Structure on Spontaneous Ignition of Hydrocarbons.

Abstract: S P O N T A N E O U S ignition properties of combustible materials, particularly fuels and hydrocarbons, have been an important area of combustion research for over 50 years. This interest in spontaneous ignition is based on the important role which this phenomenon plays in the fire hazard in the handling and storage of combustibles, the performance of various types of combustion engines, and the elucidation of oxidation and combustion mechanisms of fuels, hydrocarbons, and related substances.The spontaneous i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 11 publications
(22 reference statements)
5
23
0
Order By: Relevance
“…The AIT decreased as the chain length increased, and started to level off at the chain length of eight. This result is consistent with the result of Affens and his coworkers 5 for the effect of chain length on the AIT of hydrocarbons: the longer the chain length, the lower the AIT. The AIT of 3-chloropropyltrichlorosilane was about 368C higher than that of n-propyltrichlorosilane.…”
Section: Resultssupporting
confidence: 93%
“…The AIT decreased as the chain length increased, and started to level off at the chain length of eight. This result is consistent with the result of Affens and his coworkers 5 for the effect of chain length on the AIT of hydrocarbons: the longer the chain length, the lower the AIT. The AIT of 3-chloropropyltrichlorosilane was about 368C higher than that of n-propyltrichlorosilane.…”
Section: Resultssupporting
confidence: 93%
“…The nature of the data also hampers the development of models for the prediction of the AIT based on molecular properties alone. Affens et al (1961) used the same apparatus as Setchkin (1954) in an effort to correlate ignition behavior to chemical structure for various classes of alkane and aromatic substances. They noted some correlations between a decrease in chain length, methyl groups, unsaturation, and chain branching with an increase in the minimum AIT for aliphatic hydrocarbons as well as a correlation between existing side chains and side chain length and increased AIT for alicyclic compounds and aromatics (Affens et al, 1961).…”
Section: Autoignition Backgroundmentioning
confidence: 99%
“…Affens et al (1961) used the same apparatus as Setchkin (1954) in an effort to correlate ignition behavior to chemical structure for various classes of alkane and aromatic substances. They noted some correlations between a decrease in chain length, methyl groups, unsaturation, and chain branching with an increase in the minimum AIT for aliphatic hydrocarbons as well as a correlation between existing side chains and side chain length and increased AIT for alicyclic compounds and aromatics (Affens et al, 1961). More recently, a study by Tsai et al (2012) attempted to fit a model to the AIT of 820 compounds reported in the DIPPR database based on a set of molecular descriptors.…”
Section: Autoignition Backgroundmentioning
confidence: 99%
“…Thus, the AIT of a compound is highly affected by its molecular structure because the stability of the free radicals that are formed is related directly to the molecular structure of the compound. For hydrocarbons, decreasing the chain length, addition of methyl groups, unsaturation, branching, and cyclic and aromatic structures will elevate the AIT [18]. The relationship between the AITs of lower alkanes and their corresponding alcohols and aldehydes is in the following order: alkane > alcohol > aldehyde [17].…”
Section: Database and Group Definitionsmentioning
confidence: 99%